Implementasi Item-Based Collaborative Filtering Dalam Sistem Pemesanan Online Pada UMKM Berbasis Website - Ikhsan, Ramadhani Al; Harahap, Aninda Muliani (JURNAL RISET KOMPUTER (JURIKOM), 2025)
This study designs a web-based online menu ordering system for the UMKM Solo Fried Chicken (SFC), located on Jl. Binjai KM.10.5, Paya Geli, Sunggal District, Deli Serdang Regency. The system is built using PHP and MySQL, with a responsive design to allow customers to place orders anytime and anywhere. The applied technology aims to address several issues previously faced by UMKM SFC, such as slow and inefficient manual ordering processes, long queues, and order recording errors that affect service quality. Additional problems include the lack of available menu information, the absence of a recommendation system to assist customers in choosing menus, and the unavailability of a digital system for recording transactions and sales reports. The main problem addressed in this study is how to build a web-based online ordering system that not only simplifies transactions but also accurately recommends menus based on customer preferences. As a solution, this research implements the Item-Based Collaborative Filtering method to recommend menus based on the purchasing patterns of other customers with similar preferences. Based on the calculations, the system recommends the top three most relevant menus for each main menu item, such as Combo Original Paha for Ayam Paha, and Kidz 3, which frequently appears as a recommendation due to its similarity with many customers' preferences. This system is expected to improve operational efficiency, reduce errors, accelerate service, and provide a more personalized ordering experience. Key features developed in the system include online ordering, menu recommendations, sales reports, and transaction recording, which are visualized through a Use Case Diagram and Flowmap